A global revision of the Seahorses Hippocampus Rafinesque 1810 (Actinopterygii: Syngnathiformes): Taxonomy and biogeography with recommendations for further research - Lourie, S. A.; Pollom, R. A.; Foster, S. J. (Zootaxa, 2016)
Nomenclatural clarity is vital for the collection, dissemination, and retrieval of natural history information, which itself is necessary for effective conservation and management of species. Seahorses (genus Hippocampus) are small marine fishes that in many cases are heavily exploited and suffering severe population declines worldwide, leading to conservation concern and action. Here we provide a brief history of seahorse taxonomy, and attempt to clarify seahorse nomenclature by reducing redundancy and exposing areas of disagreement in need of further study. We provide an annotated list of the 41 species we currently recognize as valid, and describe their geographical distributions to offer a solid foundation for future research and conservation efforts. We base our conclusions on available morphological, genetic and distributional data, re-examination of the relevant literature, previous examination of almost all original type specimens, familiarity with many thousands of other live and dead specimens, and photographs of seahorses. This work should lead to greater taxonomic clarity by highlighting known research gaps and by ensuring that each species designation is justified by robust and defensible taxonomic protocols. Such clarity should facilitate greater efficacy in management and conservation.